Sandor Katz and the Possibilities of a Queer Fermentive Praxis - Maroney, Stephanie (Cuizine, 2018)
Fermentation, when embedded in queer politics, offers a conceptual and material challenge to the ideology of purism that structures dominant understandings of health in the North American context. Through a close reading of Sandor Katz’s book Wild Fermentation and the author’s experiences at a 2014 summer residency at Katz’s Foundation for Fermentation Fervor, this article contributes to food studies scholarship exploring the transformative potential of fermentation. In his teaching and writing, Katz challenges the ideology of purism through a queer fermentive praxis that advocates for improvisation, microbial inspiration, and interdependent nourishment. This praxis demonstrates an imperfect, do-it-yourself (DIY) ethos of fermentation that empowers folks to experiment with found and foraged materials. Katz’s theorization of fermentation as social change heralds the queer shape-shifting of microorganisms as inspiration for human action. And, in the context of the queer rural community where he makes his home, Katz’s fermentive praxis cultivates interdependent, inter-species nourishment. This queer fermentive praxis activates the political potential of fermentation by refusing the dominant view of human beings as individuals engaged in purity projects of control and subordination. Instead, it imagines humans as co-constituted, deeply dependent subjects who are responsible to, and in service of creating conditions for flourishing of all kinds of life.